AAV‐mediated gene delivery in Dp71‐null mouse model with compromised barriers. Issue 3 (31st December 2013) - Vacca, Ophélie; Darche, Marie; Schaffer, David V.; Flannery, John G.; Sahel, José‐Alain; Rendon, Alvaro; Dalkara, Deniz
<x xml:space="preserve">Abstract</x> Formation and maintenance of the blood–retinal barrier (BRB) is required for proper vision and breaching of this barrier contributes to the pathology in a wide variety of retinal conditions such as retinal detachment and diabetic retinopathy. Dystrophin Dp71 being a key membrane cytoskeletal protein, expressed mainly in Müller cells, its absence has been related to BRB permeability through delocalization and down‐regulation of the AQP4 and Kir4.1 channels. Dp71‐null mouse is thus an excellent model to approach the study of retinal pathologies showing blood–retinal barrier permeability. We aimed to investigate the participation of Müller cells in the BRB and in the inner limiting membrane of Dp71‐null mice compared with wild‐type mice in order to understand how these barriers work in this model of permeable BRB. To this aim, we used an Adeno‐associated virus (AAV) variant, ShH10‐GFP, engineered to target Müller cells specifically. ShH10 coding GFP was introduced by intravitreal injection and Müller cell transduction was studied in Dp71‐null mice in comparison to wild‐type animals. We show that Müller cell transduction follows a significantly different pattern in Dp71‐null mice indicating changes in viral cell‐surface receptors as well as differences in the permeability of the inner limiting membrane in this mouse line. However, the compromised BRB of the Dp71‐null mice does not lead to virus leakage into the bloodstream when the virus is injected intravitreally – an important consideration for AAV‐mediated retinal gene therapy. GLIA 2014;62:468–476